特种装置中微小型轴与齿轮装配方法可行性研究 - 刘克非; 张之敬; 金鑫; 王成林; 张虎 (Jixie chuandong)
Four assembling processes for miniature spindles and gears are advanced,based on the structural and loaded characteristics of micro-parts in the special equipment.Two schemes of them——the laser welding and interference fit——are discussed in detail.The assembling process feasibility is affirmed by FEA simulating and mount trial.